(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research aims to determine the effect of PETTLEP mental imagery training on the playing performance of volleyball athletes in extracurricular activities at MAN 3 Sukabumi. The research was carried out using a pre-experimental research type with a quantitative approach and a one group pre-test post-test design. The sample in this study consisted of 25 athletes with a sampling technique using purposive sampling. Playing performance data is collected using the Game Performance Assessment Instrument (GPAI). The results of the analysis using the pretest and posttest average difference test on the playing performance variable sig 0.00 < 0.05, meaning that Ho is rejected and H1 is accepted, so it can be concluded that there is a significant influence of PETTLEP mental imagery training on the playing performance of volleyball athletes in MAN 3 Sukabumi extracurricular.